New perspectives in functional hypogonadotropic hypogonadism: beyond late onset hypogonadism - Spaziani, Matteo; Carlomagno, Francesco; Tarantino, Chiara; Angelini, Francesco; Vincenzi, Ludovica; Gianfrilli, Daniele (Frontiers in Endocrinology, 2023)
Functional hypogonadotropic hypogonadism (FHH) is an increasingly frequent condition, whose pathological mechanisms are not yet fully clarified. The concept of FHH has now completely replaced that of late onset hypogonadism, that only concerned the ageing man. FHH is the result of an impairment of the hypothalamic-pituitary gonadal axis (HPG-A) function, resulting in decreased testosterone concentrations associated with low or inappropriately normal gonadotropin levels and infertility; it can be diagnosed once organic causes of hypogonadism are excluded. The growing occurrence of FHH derives from its association with widespread conditions, such as obesity and diabetes mellitus, but also to the increasing ease and frequency of use of several drugs, such as opioids, glucocorticoids, and sex steroids. Moreover, given the tendency of many subjects to excessive physical activity and drastic reduction in caloric intake, FHH may also be secondary to low energy availability. Finally, the association with HIV infection should not be overlooked. Therefore, there is an important variability in the diseases that can lead to FHH. Despite the heterogeneity of the underlying pathologies, the mechanisms leading to FHH would seem quite similar, with the initial event represented by the impairment at the HPG-A level.Nevertheless, many different biological pathways are involved in the pathogenesis of FHH, therefore the aim of the current paper is to provide an overview of the main relevant mechanisms, through a detailed analysis of the literature, focusing specifically on pathogenesis and clinical, diagnostic and therapeutic aspects.